The impact of the COVID-19 pandemic on influenza, respiratory syncytial virus, and other seasonal respiratory virus circulation in Canada: A population-based study - Helen E. Groves; Pierre-Philippe; Adriana Peci; Daniel S. Farrar; Steven Buckrell; Christina Bancej; Claire Sevenhuysen; Aaron Campigotto; Jonathan B. Gubbay; Shaun K. Morris (Elsevier, 2021)
Background: The ongoing coronavirus disease 2019 (COVID-19) pandemic has resulted in implementation of public health measures worldwide to mitigate disease spread, including; travel restrictions, lockdowns, messaging on handwashing, use of face coverings and physical distancing. As the pandemic progresses, exceptional decreases in seasonal respiratory viruses are increasingly reported. We aimed to evaluate the impact of the pandemic on laboratory confirmed detection of seasonal non-SARS-CoV-2 respiratory viruses in Canada. Methods: Epidemiologic data were obtained from the Canadian Respiratory Virus Detection Surveillance System. Weekly data from the week ending 30th August 2014 until the week ending the 13th March 2021 were analysed. We compared trends in laboratory detection and test volumes during the 2020/2021 season with pre-pandemic seasons from 2014 to 2019. Findings: We observed a dramatically lower percentage of tests positive for all seasonal respiratory viruses during 2020-2021 compared to pre-pandemic seasons. For influenza A and B the percent positive decreased to 0•0015 and 0•0028 times that of pre-pandemic levels respectively and for RSV, the percent positive dropped to 0•0169 times that of pre-pandemic levels. Ongoing detection of enterovirus/rhinovirus occurred, with regional variation in the epidemic patterns and intensity. Interpretation: We report an effective absence of the annual seasonal epidemic of most seasonal respiratory viruses in 2020/2021. This dramatic decrease is likely related to implementation of multi-layered public health measures during the pandemic. The impact of such measures may have relevance for public health practice in mitigating seasonal respiratory virus epidemics and for informing responses to future respiratory virus pandemics. Funding: No additional funding source was required for this study.